Persistent BK polyomavirus‐DNAemia may warrant cystoscopy to rule out urologic carcinoma: A case report and review of the literature. Issue 5 (21st May 2020) - Prom, Alyson; Jorgenson, Margaret; Alagusundaramoorthy, Sayee; Parajuli, Sandesh
Abstract: There is minimal literature describing the clinical workup of patients with persistent BKPyV‐DNAemia despite aggressive immunosuppressive reduction. We present a case herein of persistent BKPyV‐DNAemia with significant discordance of BK viruria level in a kidney transplant recipient found to have bladder carcinoma. Based on our findings, we recommend evaluating the urine of patients with persistent BKPyV‐DNAemia for BK viruria. If there is significant discordance in the level of BKPyV‐DNAemia and viruria, cystoscopy should be pursued to rule out bladder or uroepithelial malignancies.